Synthesis and characterization of layer-aligned poly(vinyl alcohol)/graphene nanocomposites - Yang, Xiaoming; Li, Liang; Shang, Songmin; Tao, Xiao-ming (Polymer (Guilford), 2010)
Layer-aligned poly(vinyl alcohol)/graphene nanocomposites in the form of films are prepared by reducing graphite oxide in the polymer matrix in a simple solution processing. X-ray diffractions, scanning electron microscopy, Fourier-transform infrared spectroscopy, differential scanning calorimetry and thermogravimetric analysis are used to study the structure and properties of these nanocomposites. The results indicate that graphene is dispersed on a molecular scale and aligned in the poly(vinyl alcohol) (PVA) matrix and there exists strong interfacial interactions between both components mainly by hydrogen bonding, which are responsible for the change of the structures and properties of the PVA/graphene nanocomposites such as the increase in Tg and the decrease in the level of crystallization. [Display omitted]